Screening for ecotoxicological effects of antiepileptic drugs in biologically treated waste water originating from an epilepsy ward by Danio rerio embryos - Hartwig, Christoph; Muth-Köhne, Elke; Düring, Rolf-Alexander; Justus Liebig University Giessen (My University, 2013)
Background: Pharmaceuticals, like antiepileptic drugs, are found regularly in surface waters, and consequently, advanced waste water treatment technologies are discussed for substance elimination. Because antiepileptic drugs have shown to transform to more toxic substances, their behavior in these treatment processes and resulting effects on ecotoxicity should be investigated. To validate if waste water from an epilepsy ward of a neurological hospital is appropriate for these investigations, it was treated with a membrane bioreactor (MBR), analyzed for antiepileptic drugs and screened for ecotoxicological effects with Danio rerio embryos. Further, the behavior of antiepileptic drugs in MBR treatment was estimated.Results: Treatment of raw hospital waste water by the pilot scale MBR was successful regarding the low dissolved organic carbon concentration in the effluent and allowed ecotoxicological testing with D. rerio. According to the estimated behavior, partial elimination of 10-hydroxy-10,11-dihydrocarbamazepine (10-OH carbamazepine) and rufinamide and some release of lamotrigine, oxcarbazepine and, possibly, primidone occurred. The other investigated substances did not considerably change concentrations due to treatment. The highest concentrated substances found were 10-OH carbamazepine, lamotrigine, and oxcarbazepine. The complex mixture of the treated waste water had no effect on D. rerio morphology and did not change its primary and secondary motor neurons (indicator for developmental neurotoxicity). Oxcarbazepine did not show morphological effects on D. rerio at 8.7 mg L−1.Conclusions: Biological treatment was not sufficient to significantly eliminate the load of antiepileptic drugs investigated. No effects on D. rerio embryos were observed. Biologically treated waste water, originating from an epilepsy ward, is appropriate for the investigation of the fate of antiepileptic drugs in advanced treatment processes.
Keywords: Oxcarbazepine; MBR; Membrane bioreactor; Hospital; Fish; Motor neurons; LC-TOF-MS; ddc:630